Almost always observable hybrid systems. (May 2020) - Arbib, Claudio; De Santis, Elena
Abstract: For a class of hybrid systems we introduce and characterize the almost always observability property, i.e. the possibility of reconstructing the current continuous component of the state, from the observed output, for almost all switching times. The optimal location of additional sensors that make the system almost always observable is investigated.